The Hudson's Bay Company versus Magna Charta, and the British people [electronic resource] - Liverpool Financial Reform Association. (Liverpool : The Association; London : P.S. King, 1857)
Original issued in series: Financial reform tracts. New series no. 21. '"Grants of Monopolies are against the ancient and fundamental laws of the Kingdom"--Ibid, p. 181.' '"All Monopolies concerning Trade and Traffic ."--Coke's Institutes, vol. I, p. 62.' Electronic reproduction. Mode of access: Internet. 44